Social and health aspects of patients co-infected with HIV/tuberculosis - Larissa de Araújo Lemos; Alexsandra Rodrigues Feijão; Marli Teresinha Gimeniz Galvão (Universidade Federal do Ceará, 2013)
The aim was to assess the social and health aspects and perception about the diagnosis of individuals co-infected with HIV/tuberculosis. This descriptive study, with quantitative-qualitative approach was accomplished at a referral hospital in Fortaleza, Ceará, Brazil, between January and April 2009, using semistructured interviews held in a private environment. Data were analyzed descriptively and through content analysis. Participants were 16 patients co-infected with HIV/tuberculosis, 56.25% male. The predominant age range was between 31 and 39 years (43.75%), education levels were low and the monthly family income was approximately one minimum wage. Pulmonary tuberculosis was the predominant form (62.50%). Patients' perception about the discovery of the co-infection was demonstrated through two categories: Fear and anguish in view of the diagnosis and Changes in health habits and lifestyle. In view of the findings, there is an urgent need to promote these patients' psychological and physical wellbeing through political and health actions.